PERBANDINGAN EFEKTIFITAS MEDIA PENYULUHAN POSTER DAN KARTUN ANIMASI TERHADAP PENGETAHUANKESEHATAN GIGI DAN MULUT (Studi pada Siswa/i Kelas V SDN 24 Kota Banda Aceh) - Poppy Andriany; Cut Fera Novita; Summiyati Aqmaliya (Journal of Syiah Kuala Dentistry Society, 2016)
Dental Health among children generally indicated by bad oral hygiene that usually caused by the the less knowledge of dental health information. The upgrading of dental health could be done by dental health education. Dental health education usually using aids to draw attention and motivation about the content of learning. The aim of this study is to determine the effectiveness of poster and cartoon animation to gain the knowledge of dental health education. This study is a- quasi-experimental with pretest and posttest group design to the 5th grade student of SDN 24 Banda Aceh City. This study is using total sampling that devided to poster group aids and cartoon animation group aids, each group will be compare both pretest and posttest by using questionare and the average score by each group aids will be compare to. This study is using analytic descriptive univariate and bivariate. The result of this study is significan increasing score of knowledge both of group aids (p0,05). The conclusion of this study is dental health education using both of group aids showing the better result than without the aids, furthermore cartoon animation aids is more effective than poster aids to upgradedental health for the 5th grade primary school SDN 24 Banda Aceh City.Keywords : Knowledge, Children Dental Health, Dental Health Education, Poster, Cartoon Animation.